Integrasi Kepemimpinan Transformasional, Transaksional, Dan Profetik Dalam Meningkatkan Efektivitas Organisasi Pendidikan Islam - Salsabila, Aulia Nursekha; Nugraha, Mulyawan Safwandy (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study examines the integration of transformational, transactional, and prophetic leadership styles in improving organizational effectiveness at Madrasah Aliyah Negeri 5 Garut. Using a qualitative case study approach conducted from September 25-29, 2025, data were collected through in-depth interviews with principals, vice principals, senior and junior teachers, administrative staff, and students, complemented by observation and document analysis. The findings reveal that the principal predominantly applies transformational leadership through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, supported by transactional elements (contingent reward and management by exception) and prophetic values (shiddiq, amanah, and shura). The strengths lie in inspirational leadership oriented toward Islamic educational vision, moral exemplary, innovation encouragement, empathy, and integration of religious and professional values. However, weaknesses persist in uneven participation in deliberation, inconsistent reward systems, leadership centralization, and administrative-focused transactional approaches. Five priority interventions are recommended: transformation toward distributed leadership, development of innovation culture, strengthening communication and participation systems, organizational justice management, and generational bridging programs. The implementation strategy is designed in three phases over twelve months with comprehensive evaluation and monitoring systems to ensure sustainable organizational transformation.